A multi-criteria CCUS screening evaluation of the Gulf of Mexico, USA. (July 2022) - Wendt, Anna; Sheriff, Alana; Shih, Chung Yan; Vikara, Derek; Grant, Tim
Highlights: Developed a screening method for ranking viable offshore CO2 storage sites. Evaluation incorporates disparate spatial GIS data in decision-making framework. 14 GIS criteria aggregated over 2559 spatially balanced points across GOM OCS. Highest ranking regions for storage located along LA coastline in shallow waters. Highest ranking regions for EOR located in central GOM OCS and MS River Delta. Abstract: Continued research into reservoir characterization along with offshore carbon dioxide (CO2 ) transportation and infrastructure assets is needed to facilitate development of safe and successful carbon capture, utilization, and storage (CCUS) projects. This paper outlines a multi-criteria evaluation methodology that incorporates disparate sets of quantitative, spatially variable data into a decision-making framework for screening the Gulf of Mexico (GOM) outer continental shelf (OCS) for potentially viable CO2 storage and enhanced oil recovery (EOR) sites. Criteria categories include favorable geologic characteristics, logistics, and potential risks. Data compiled for 14 criteria from several publicly available geographic information system (GIS) layers was aggregated over 2559 spatially balanced points across the study area using the National Energy Technology Laboratory (NETL)-developed Cumulative Spatial Impact Layers™ (CSIL) GIS tool. Criteria are weighted by qualitative expert opinion relative to their perceived importance to given scenarios— the output of combined criteria values and weights enables regional CO2 storage suitability differentiation. The methodology considers both technical and non-technical factors impacting CCUS decision-making. The flexible methodology enables a systematic approach to regional ranking at high spatial resolution over a large study domain. Additionally, the framework enables high-grading of priority sites that warrant further characterization and follow-on analysis. Areas along the Louisiana coast and Mississippi River Delta consistently rank high for all scenarios largely a result of the favorable geology with the potential for stacked storage, as well as the density of existing pipelines and platforms, and proximity to several onshore CO2 sources. High-graded regions for the CO2 EOR-related scenarios are typically located further offshore towards the middle and edge of the OCS compared to higher priority regions for the geologic storage scenarios which fall closer to the Louisiana coastline.